Obtenção, caracterização e estudo do comportamento térmico de 8-hidroxiquinolinatos de ferro e manganês - Rossatto, Fabiana Maria (2020)
High-performance ceramic materials have been attracting interest in the technological and scientific community due to their advantages and properties that can be modified. Ferriteshave stood out for having magnetic, electrical, optical and catalytic properties. In the literature, there are several methods of synthesis of oxides, such as solid state, polymeric precursors, sol-gel and chemical precipitation. However, the methodology considerably influences the characteristics of the final compound. This study presents the results of the synthesis, characterization and thermal behavior of iron and manganese 8-hydroxyquinolinates where 8-hydroxyquinoline (8-HQ) is used as a chelating agent and the methodology is based on the chemical precipitation method. Thus, it is possible to divide the work into three stages: the first stage is the synthesis of the chelate from iron and manganese nitrates with 8-HQ, with a pH adjusted to 8.5 using ammonium hydroxide (NH4OH). After filtered, dried and macerated, the precipitate was characterized by X-Ray Diffractometry (XRD), Fourier Transform Infrared Spectroscopy (FTIR) and Scanning Electron Microscopy with X-Ray Dispersion Spectroscopy (SEM/EDS). The second stage is the study of the thermal behavior of the chelate using the techniques of Thermogravimetric Analysis (TGA), Differential Thermal Analysis (DTA) and Derivative Thermogravimetry (DTG). And the third stage is the calcination of the material at a temperature of 400°C for 10 hours, in addition to the final temperatures of 400, 500, 600, 700, 800, 900, 1000, 1100 and 1200 ºC and further characterization using the techniques of XRD with refinement by the method of Rietveld, FTIR and MEV/EDS. Based on the results of the analyzes, it is suggested that the formation of chelates Mn(8-HQ)2and Fe(8-HQ)3occurred, with the thermal study it is possible to observe that at temperatures between 400 and 550 ºC events still occur of mass variation and peaks of manganese spinel ferrite (MnFe2O4) are observed in samples MnFe400-10h, MnFe800, MnFe900, MnFe1000, MnFe1100 and MnFe1200, the latter being in greater quantity, composing the sample in 13.32%. Therefore, as it is a simple methodology, the synthesis process can be very promising for the production of MnFe2O4spinel